2019
DOI: 10.1021/acs.chemmater.9b03329
|View full text |Cite
|
Sign up to set email alerts
|

Designing High Performance Nonfullerene Electron Acceptors with Rylene Imides for Efficient Organic Photovoltaics

Abstract: Improving carrier mobility, redox stability, blend morphology, and photovoltaic performance while elucidating structure–property relationships remains an important design goal for nonfullerene electron acceptors (NFAs) for organic solar cells. Although numerous NFAs have been created from rylene diimide electron-deficient building blocks, they have shown far inferior photovoltaic properties compared to benchmark fused-ring electron acceptors (FREAs) such as ITIC. Herein we show that new bis­(naphthalene-imide)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Typically, A-D-A type acceptors can be reasonably designed and regulated through fused core variation, 69,76-86 side chain engineering, [87][88][89][90] and end group modification. 11,73,[91][92][93][94][95][96][97][98] As such, similar strategies can be also applied to design novel A-DA 0 D-A type acceptors, especially the big Y family. In the following text, we will elaborate on these molecular design strategies with selected examples.…”
Section: Molecular Structures and Packingsmentioning
confidence: 99%
“…Typically, A-D-A type acceptors can be reasonably designed and regulated through fused core variation, 69,76-86 side chain engineering, [87][88][89][90] and end group modification. 11,73,[91][92][93][94][95][96][97][98] As such, similar strategies can be also applied to design novel A-DA 0 D-A type acceptors, especially the big Y family. In the following text, we will elaborate on these molecular design strategies with selected examples.…”
Section: Molecular Structures and Packingsmentioning
confidence: 99%
“…[20][21][22][23] Among them, PFN-based polymers are limited in further processing considerations due to strict thin thickness (5-10 nm). [24] Derivatives of imide and amine-substituted small molecules or polymers are prime examples that have received extensive attention as cathode interlayers in OSCs due to high electron affinity and mobility, [25][26][27][28] especially for NDI-and PDIbased conjugated small molecules. [15,[29][30][31][32] However, the imidebased interlayer materials have inevitably verbose multistep synthesis and tedious purification steps.…”
Section: Introductionmentioning
confidence: 99%
“…Kolhe et al [45] reported earlier this year the synthesis of a novel NFA, a3, which contains the unusual naphthaleneimide mono-ketone as the electron rich end-capping group. A3 showed an absorption maximum at a lower wavelength with respect to a2, demonstrating that the modified naphthalene imide does not possess an optimal electron withdrawing character.…”
Section: Modification Of Electron-deficient End-capping Groupsmentioning
confidence: 99%